Case control study to identify the risk factors of chronic kidney disease - ELIZABETH SHANTI ABRAHAM; SHEELA PAVITHRAN; RAHUL R (International Journal of Pharma and Bio Sciences, 2017)
Chronic Kidney Disease (CKD) is a global issue and its risk factors differ between races and countries. The increase in incidence of CKD in the last decade attributes to the lifestyle changes which need to be identified. It is worth understanding the risk factors in India where there is diversity in the income, food, cultural traditions and lifestyle habits. This “case control study to assess the risk factors of chronic kidney disease among adults” was conducted among 200 subjects with the objectives to identify the risk factors of chronic kidney disease and to estimate the exposure to risk factors among patients with and without chronic kidney disease using retrospective survey design. The data were collected using a structured questionnaire and analysed using Odd’s ratio (OR). The findings show that age (OR-2.6675, CI-95%, 1.443-4.957) and family history of CKD (OR-4.846, CI-95%, 1.020-23.0228) were the non-modifiable risk factors. Co-morbidities like hypertension (OR-18.971, CI-95%, 9.235-38.969), diabetes mellitus (OR-3.618, CI-95%, 2.017-6.490), coronary artery disease (OR-11.821, CI-95%, 4-34.933), urinary tract infections (OR-5.664, CI-95%, 2.460-13.043) and use of analgesics (OR-6, CI-95%, 2.186-16.467) were major modifiable risk factors. Modifiable risk factors play an important role in the development of CKD. So screening the patients at risk for CKD should be emphasized and treating the modifiable risk factors at an early stage will help to reduce the incidence and or progression of the disease. Prevention and control should also focus on the life style habits.